PENGEMBANGAN LKPD DIGITAL MENGGUNAKAN WORDWALL PADA SUBTEMA KEKAYAAN SUMBER ENERGI DI INDONESIA - Cahyati Ningrum, Putri; Novita, Lina; Safitri, Nurlinda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
The digital LKPD is a guideline for Digital Student Worksheets. It makes it easier for students to participate in digital learning activities designed through wardwall, which can be accessed on various platforms. This research aims to develop a digital LKPD using Wordwall on the subtheme of energy resource wealth in Indonesia. Research and Development (R&D) research method using the ADDIE (Analysis, Design Development, Implementation, and Evaluation) model approach. This research was carried out at SDN Pasir Tengah 01 grade IV. Based on the results of the validity of the development of the LKPD Digital Wardwall, the subtheme of energy resource wealth in Indonesia obtained a validity level of 97.77% from material experts with a very feasible category, linguists with a very feasible category of 98% and media experts with a fairly valid category of 80%. Meanwhile, the results of the student response questionnaire as users obtained a percentage of the practicality of 85%. Thus, it can be concluded that the digital LKPD using Wordwall on the subtheme of energy resource wealth in Indonesia is declared feasible and can be used in the learning process of the energy resource wealth subtheme in Indonesia so that student activities are involved in the teaching and learning process.